Implementation Of Continuing Education Programs In The Process Of The International Integration; The European Proceedings of Social & Behavioural Sciences (EpSBS); Vol. 38 : Lifelong Wellbeing in the World (WELLSO 2017) - Zhuravleva I. Irina; Kuznetsova O. Olga; Kuznetsov V. Vladimir; Galtseva (Gal’tseva) O. V. Olga Valerievna; Muratov K. Kamil (2018, 2018)
Title screen